2016
DOI: 10.1039/c6ra18747a
|View full text |Cite
|
Sign up to set email alerts
|

Stable solar-driven water splitting by anodic ZnO nanotubular semiconducting photoanodes

Abstract: The development of high performance artificial photosynthetic devices, to store solar energy in chemical bonds, requires the existence of stable light-absorbing electrodes for both the oxidative and reductive half-reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 33 publications
0
32
0
Order By: Relevance
“…Furthermore, the O 1s spectra (Figure 2d), revealing a singlet peak at 531.2 fitted into two main peaks at 531.6 and 532.4 eV, respectively. The first peak at 531.6 eV characteristic of oxygen ions in the metal oxide lattice, and the second peak at 532.4 eV can be related to the O−H bonding [6,36–38] …”
Section: Figurementioning
confidence: 99%
“…Furthermore, the O 1s spectra (Figure 2d), revealing a singlet peak at 531.2 fitted into two main peaks at 531.6 and 532.4 eV, respectively. The first peak at 531.6 eV characteristic of oxygen ions in the metal oxide lattice, and the second peak at 532.4 eV can be related to the O−H bonding [6,36–38] …”
Section: Figurementioning
confidence: 99%
“…34,35 In recent years, it has been reported that various ZnO nanostructures can be prepared by the anodization technique using some suitable simple solutions such as NaOH, KHCO 3 , NH 4 Cl/ H 2 O 2 , H 2 SO 4 and ethanolic HF solutions. 15,34,[36][37][38] Nanotube morphology with high surface volume ratio among different morphologies draws attention due to its widespread application area. ZnO nanotube morphologies produced using sulfur-based electrolytes have been few reported.…”
Section: Introductionmentioning
confidence: 99%
“…While nanostructured metal oxides can be easily produced on the surfaces with the anodization technique of many metals such as Al, Ti and Zr, regular ZnO nanomorphology cannot be prepared easily due to the instability in both acidic and alkaline solutions 34,35 . In recent years, it has been reported that various ZnO nanostructures can be prepared by the anodization technique using some suitable simple solutions such as NaOH, KHCO 3 , NH 4 Cl/H 2 O 2 , H 2 SO 4 and ethanolic HF solutions 15,34,36‐38 . Nanotube morphology with high surface volume ratio among different morphologies draws attention due to its widespread application area.…”
Section: Introductionmentioning
confidence: 99%
“…The catalyst hierarchical morphology can supply high surface roughness, large surface‐to‐volume ratio. Thus, various nanomorphologies such as wires, plates, rods, spheres, and flowers have been reported . Nanoflower morphology is an effective two‐dimensional (2D) structure producing a high surface area, high catalytically active sites, and low electron and ion transport paths resulting in improved catalytic activity …”
Section: Introductionmentioning
confidence: 99%
“…Thus, various nanomorphologies such as wires, plates, rods, spheres, and flowers have been reported. [20,21] Nanoflower morphology is an effective two-dimensional (2D) structure producing a high surface area, [22] high catalytically active sites, and low electron and ion transport paths resulting in improved catalytic activity. [23,15] In this study, a facile and efficient synthesis strategy of the hierarchically structured NiCo 2 O 4 nanoflowers is reported.…”
Section: Introductionmentioning
confidence: 99%